Teacher Problems in Implementing Google Classroom - Selvia, Devi Sela Eka; Suri, Indah Resti Ayuni (Universitas Islam Negeri Raden Intan Lampung, 2022)
Google Classroom is used to manage the learning system at the school to college level. With Google Classroom, teachers can effectively and efficiently manage classrooms. This research was conducted to describe the teachers’ problems in implementing learning using Google Classroom on the Al-Qur'an Hadith subject at MTs Negeri 2 Bandar Lampung. This research is field research with a qualitative approach. To obtain the necessary data, the researchers conducted interviews and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed the teachers’ problems in implementing learning using Google Classroom on Al-Qur'an Hadith subject at MTs Negeri 2 Bandar Lampung. Islamic Religious Education teachers explained the problems experienced using this Google Classroom, such as attendance, active learning and motivation learning. The efforts made by Islamic Religious Education teachers are reducing the KKM (Criteria of Minimum Mastery) and performing collaboration between Islamic Religious Education teachers, BK (counselling) teachers, and homeroom teachers. So it can be concluded that in using Google Classroom, teachers must properly design from the planning, implementation and evaluation stages of learning so that learning becomes effective.